The Effect of Balanced Diet on Adolescent Health: A Literature Study - Firayani, Firayani (Journal Nutrizione, 2024)
A balanced diet plays an important role in supporting adolescent health and development. Adolescence is characterized by rapid physical growth and complex psychological and social changes, so that nutritional needs are higher than in childhood. This literature study aims to comprehensively examine the effect of a balanced diet on the physical, mental, and social health of adolescents based on the latest scientific findings. This study uses a qualitative method with a literature study approach to scientific articles published in the last five years. The results of the study indicate that a balanced diet that includes the right intake of macronutrients and micronutrients contributes to optimal growth, endurance, cognitive function, and emotional stability. Conversely, an unbalanced diet is closely related to various health problems such as obesity, anemia, mental disorders, and decreased academic achievement. These findings indicate that integrated educational interventions and nutrition policies are urgently needed among adolescents to support the creation of a holistically healthy generation.